A Field Research as an Anthropological Tool in Literary Reportage (on the Examples of Journalistic Texts by Joseph Roth) - Яремчук, Олеся Любомирівна (Київський національний університет імені Тараса Шевченка, 2019)
This article studies the use of field research as an anthropological tool in literary reportage which is a comprehensive element of the creation of journalistic content. Based on the examples of journalistic texts of the 20s by the Austrian writer Joseph Roth, we have analyzed the anthropological methods which were used by this author in his reportages, that is the main objective of this study. Using diachronic comparison, qualitative method and content analysis to evaluate and to explain the concept of Joseph Roth’s texts, as well as the methodology of textual, syntagmatic (by Volodymyr Propp) and paradigmatic analysis (by Claude Levi-Strauss), we have examined the generated meanings in the texts of the mentioned author. As a result of the study, we have identified four methods that Joseph Roth used writing his news reportages in the 1920s, including “In Midday France” and “White Cities”. Those methods are as follows: overt observation, in-depth interviews, fixing details and gaining empirical experience. The modern authors call these methods as classic ones, without which it is impossible to work in this genre. As we have seen from the examples of literary reportages of the French cycle by Joseph Roth, the anthropological tools used by this author for his works contributed to deepening and improving the quality of his texts which is of great significance for our study. Joseph Roth created a panoramic picture of the twentieth century in his texts through watching, communicating and studing. However, it is worth to add that he was often too subjective, suffering harsh criticism for this.

У статті досліджено використання у літературних репортажах польового дослідження як антропологічного інструменту, яке є повноцінним елементом створення журналістських матеріалів. Метою цієї наукової публікації є визначення антропологічних методів у репортерських текстах 20-х років Йозефа Рота, австрійського письменника та репортера, народженого у Бродах. Використовуючи діахронне порівняння, якісний метод та контентаналіз для оцінювання та пояснення концепції текстів Йозефа Рота, а також методологію текстуального, синтагматичного (за Володимиром Проппом) та парадигматичного аналізу (за Клодом Леві-Стросом), досліджено згенеровані значення у текстах згаданого автора. Внаслідок дослідження виокремлено чотири методи, до яких вдавався Йозеф Рот, пишучи цикли репортажів 20-х років, зокрема «У полудневій Франції» та «Білі міста». Це включене спостереження, глибинне інтерв’ю, фіксування деталей та здобуття емпіричного досвіду. Ці фактори сучасні автори називають класичними, без яких робота у цьому жанрі неможлива. Як можна побачити на прикладах літературних репортажів французького циклу Йозефа Рота, антропологічні інструменти, які автор використовував для своєї роботи, посприяли поглибленню та якості його текстів. Спостерігаючи, комунікуючи, досліджуючи, у своїх текстах Йозеф Рот створював панорамну картину епохи ХХ століття. Однак, варто додати, часто був надто суб’єктивним, на що гостро звертають увагу його критики.
Польове дослідження як антропологічний інструмент у літературному репортажі (на прикладах журналістських текстів Йозефа Рота)
Keywords: літературний репортаж; подорожня антропологія; польове дослідження; literary reportage; travel anthropology; field research